Investment Facilitation for Development and the Reform of International Investment Dispute Settlement Mechanism: The Choice of Developing Countries. (1st September 2022) - Tang, Yanyan
ABSTRACT: The trend of 'investment facilitation' is increasingly attracting lively discussions in the field of international investment policies. The reason for this is that countries expect to use 'investment facilitation' as a policy tool to improve the domestic investment environment. In this trend, as an important part of the realization path of 'investment facilitation', there is an increasing concern on how to reform the international investment dispute settlement mechanism to achieve amicable settlement of investment frictions between investors and host states. China, Brazil and South Africa have proposed three different options for reforming the international investment dispute settlement mechanism under the trend of 'investment facilitation'. Based on the analysis of the three countries' dispute settlement mechanism reform models, this article examines their impact on the international investment governance mechanism and finally proposes inspirations for the design and reform of future international investment dispute settlement models in developing countries.